Netropolis 2003-2006 - Najjar, Michael (Bitforms Gallery, USA; Galerie Guy Bartschi, Geneva; Galeria Fernando Silio, Spain, 2006)
This exhibition is an exploration of the way global cities will develop in the future, of similar magnitude to the impact of the industrial revolution in the late 19th century. The "netropolis" series of works portrays the megacities of Beijing, Berlin, Dubai, Hongkong, London, Mexico, New York, Paris, Sao Paulo, Shanghai and Tokyo.
English - Spain
Keywords: N4390-5098 Visual Arts. Exhibitions; Urban settlements